1071. Impact of Standard vs. Prolonged Courses of Antibiotics for the Treatment of Uncomplicated Staphylococcus aureus Bacteremia (SAB) in Patients With Hematologic Malignancies. (26th November 2018) - Cheung, Edna; McKenzie, Matt G; Colon, Lydia Benitez; Kaye, Keith S; Petty, Lindsay; Martin, Emily T; Marini, Bernard L; Perissinotti, Anthony J; Eschenauer, Gregory; Alaniz, Cesar; Wallace, Katie L; Patel, Twisha S
Abstract: Background: The optimal treatment duration for uncomplicated SAB (U-SAB) is unknown in patients with hematologic malignancies. The goal of this study was to evaluate the impact of antibiotic duration on outcomes in patients with hematologic malignancies and U-SAB. Methods: This was a multicenter, retrospective cohort study of adult patients with hematologic malignancies and U-SAB treated with standard (2 weeks) or prolonged (>2 weeks) antibiotic therapy. U-SAB was defined as defervescence and culture clearance within 96 hours of index culture and the absence of: endocarditis, implanted prostheses, metastatic sites of infection, and bone/joint involvement. Patients with SAB therapy <10 days and those with inadequate source control were excluded. The primary outcome was a composite global clinical cure: absence of relapse SAB, absence of SAB progression, and survival at 60 days following index SAB. Results: Of 89 included patients, 51% received a standard antibiotic duration for U-SAB. The median age of the entire cohort was 56 and majority was male (60%). Neutropenia was present at index culture in 53% of patients, and acute leukemia (48%) and lymphoma (26%) were the most common underlying malignancies. Other baseline characteristics were similar between the two groups except more patients in the standard duration group had relapsed/refractory malignancy (51% vs. 25%, P = 0.016), central-line source (71% vs. 48%, P = 0.032), and antibiotic prophylaxis prior to index SAB (42% vs. 18%, P = 0.021). Median duration of treatment in the standard group was 15 days vs. 28 days in the prolonged duration group. No differences in global clinical cure and other clinical outcomes were seen between groups (Figure 1). On multivariable logistic regression analysis, only relapsed/refractory malignancy was identified as an independent predictor of global clinical failure (odds ratio, OR, 9.43; 95% confidence interval, CI, 1.17–76.9; P = 0.035). Duration of treatment was not associated with global clinical cure (OR, 2.92; 95% CI, 0.51–16.7; P = 0.23). Conclusion: No differences in clinical outcomes were seen in patients with active hematologic malignancies who received 2 weeks vs. >2 weeks of antibiotic therapy for the treatment of U-SAB, although confirmation of our findings in a larger study is warranted. Disclosures: All authors: No reported disclosures.